NILAI TAMBAH PENGOLAHAN UBI KAYU (Manihot esculenta Crantz) MENJADI KELANTING SEBAGAI SNACK LOKAL - Tri Widiastuti; Siti Nurdjanah; Tanto Pratondo Utomo (Faculty of Agricultural Technology, University of Jember, 2020)
Processing cassava into various food products is an effort to produce the economic added value of cassava. The processing also needed to reduce the damage of fresh cassava. This study was aimed to asses the performance of ‘kelanting’ as an indigenous snack and its added value. Data were collected at the Plamboyan Farmer Women's Small Group (KWT) in Rejomulyo Village, Palas Subdistrict, South Lampung Regency from August 2019 to November 2019 using questionnaire. The descriptive analysis used to describe the industry performance, while the added value calculated quantitatively using Hayami Table. The results showed that the performance of the processing of cassava by the Plamboyan Small Women Farmers Group (KWT) was affected by the high availability of raw materials, i.e. ‘mentega’ cassava as local variety and how to process ‘kelanting’. The added value of processing cassava become ‘kelanting’ was Rp 5,493.00/kg with a value-added ratio of 64.55% which was classified as high value-added (>40%). The profit was Rp. 3,743.00/kg with profit rate of 68.14%. Keywords: added value, cassava, processed cassava product